Prevalence of Ascaridia galli, Heterakis gallinarum and Tapeworm Infections in Birds Slaughtered in Makurdi Township - Ogbaje, C.I.; Agbo, E.O.; Ajanusi, O.J. (International Journal of Poultry Science, 2012)
A survey was conducted to determine the prevalence of gastrointestinal helminthes in local chickens, broilers and layers slaughtered in Makurdi metropolis between September 2007 and April 2008. A total of 440 samples were collected from male and female chickens. Of the total samples examined, 200(45.5%) were from domestic chicken, 140(31.8%) from broilers and 100(22.7%) from layers. Of the total sample examined, 280(63.6%) were infected with one or more species of helminthes. Of the number positive for infections, 103(23.4%) had single infection, 105(23.9%) double infections and 60(13.6%) triple infections. Overall, 165(37.5%) of the samples had Ascaridia galli, 122(27.7%) had Heterakis gallinarum and 214(48.6%) had various tapeworm species. Out of the 200 samples from domestic chickens, 110(55%) were found infected with Ascaridia galli, 80(40%) with Heterakis gallinarum and 145(72.5%) with different tapeworm species. Of the 140 gastrointestinal tracts from broilers, 50(35.7%) were infected with Ascaridia galli, 40(28.6%) with Heterakis gallinarum and 60(42.9%) with various tapeworm species. Out of the 100 gastrointestinal tracts from layers, 5(5%) were infected with Ascaridia galli, 2(2%) with Heterakis gallinarum and 9(9%) with various tapeworm species. The species of tapeworm encountered were Raillietina species, Choanotaenia species and Hymenolepis species. These respective species constitute 30.9%, 5.2% and 3.6% of the tapeworm burdens. This study has highlighted the need for proper medication in flocks in Makurdi.